Niobium-zirconium chronometry and early solar system development. - Schönbächler, M; Rehkämper, M; Halliday, A; Lee, D; Bourot-Denise, M; Zanda, B; Hattendorf, B; Günther, D (2002)
Niobium-92 (92Nb) decays to zirconium-92 (92Zr) with a half-life of 36 million years and can be used to place constraints on the site of p-process nucleosynthesis and the timing of early solar system processes. Recent results have suggested that the initial 92Nb/93Nb of the solar system was high (>10(-3)). We report Nb-Zr internal isochrons for the ordinary chondrite Estacado (H6) and a clast of the mesosiderite Vaca Muerta, both of which define an initial 92Nb/93Nb ratio of approximately 10(-5). Therefore, the solar system appears to have started with a ratio of <3 x 10(-5), which implies that Earth's initial differentiation need not have been as protracted as recently suggested.